1988
DOI: 10.1007/bf00330494
|View full text |Cite
|
Sign up to set email alerts
|

The repeat domain of Escherichia coli haemolysin (HlyA) is responsible for its Ca2+-dependent binding to erythrocytes

Abstract: The haemolysin protein (HlyA) of Escherichia coli contains 11 tandemly repeated sequences consisting of 9 amino acids each between amino acids 739 and 849 of HlyA. We removed, by oligonucleotide-directed mutagenesis, different single repeats and combinations of several repeats. The resulting mutant proteins were perfectly stable in E. coli and were secreted with the same efficiency as the wild-type HlyA. HlyA proteins which had lost a single repeat only were still haemolytically active (in the presence of HlyC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
2
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 24 publications
3
174
2
3
Order By: Relevance
“…Various reports have linked the RTX domain to target membrane binding (13,14). In addition we had found that the sequence 914 -936, located very close to that domain, inter- acted specifically with ␣-glycophorin, an HlyA receptor in human erythrocytes (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports have linked the RTX domain to target membrane binding (13,14). In addition we had found that the sequence 914 -936, located very close to that domain, inter- acted specifically with ␣-glycophorin, an HlyA receptor in human erythrocytes (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…We had also shown that a short sequence in the C-terminal domain (aa 914 -936) was the main HlyA region recognizing the ␣-glycophorin receptor (10), and earlier reports suggested that the nonapeptide repeat, calcium-binding region was involved in the early stages of receptor/membrane binding by HlyA (13,14). It was therefore decided to clone and express the nonapeptide repeat region, to study its properties in the absence of the amphipathic helix domain.…”
mentioning
confidence: 99%
“…Site-directed mutagenesis studies have indicated that negatively charged residues could be important (Stanley et al, 1991;Kenny e t al., 1992). A feature seen in most proteins secreted by a haemolysinlike mechanism is the presence of repeats of the sequence GGXGXD that are involved in calcium binding (Ludwig et al, 1988;Akatsuka et al, 1994). The relevance of these repeats for export is, however, unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Protein similarity searches revealed extensive similarity to a large family of secretory proteins, which includes the RTX-toxins, extracellular zinc proteases and various bacterial exoproteins (Ludwig et al, 1988). All these proteins contain a variable number of tandem repeats of a nine amino acid motif rich in glycine, aspartic acid and asparagine.…”
Section: Amino Acid Sequence Analysismentioning
confidence: 99%